2009
DOI: 10.1111/j.1530-0277.2009.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

GDNF is an Endogenous Negative Regulator of Ethanol‐Mediated Reward and of Ethanol Consumption After a Period of Abstinence

Abstract: Background We previously found that activation of the glial cell line-derived neurotrophic factor (GDNF) pathway in the ventral tegmental area (VTA) reduces ethanol-drinking behaviors. In this study, we set out to assess the contribution of endogenous GDNF or its receptor GFRα1 to the regulation of ethanol-related behaviors. Methods GDNF and GFRα1 heterozygote mice (HET) and their wild-type littermate controls (WT) were used for the studies. Ethanol-induced hyperlocomotion, sensitization, and conditioned pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 69 publications
4
42
0
Order By: Relevance
“…Moreover, because of the growth factor's ability to induce its own mRNA expression He & Ron, 2006), the reduction of alcohol drinking persists for up to 48 hours following a single intra-VTA infusion of the growth factor Carnicella et al, 2008;. Interestingly, we found that the GDNF heterozygote knockout (HET) mice consumed more alcohol than their WT littermates after a period of abstinence and exhibit increased CPP for alcohol (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009), suggesting an important role for the endogenous growth factor in the regulation of alcohol intake. To this end, we recently demonstrated that both the mRNA and protein levels of GDNF are increased in the VTA of rats after the first week of the 20% 2BC alcohol-drinking procedure (Ahmadiantehrani, Barak, & Ron, 2013).…”
Section: Protective Signaling Pathwaysmentioning
confidence: 87%
“…Moreover, because of the growth factor's ability to induce its own mRNA expression He & Ron, 2006), the reduction of alcohol drinking persists for up to 48 hours following a single intra-VTA infusion of the growth factor Carnicella et al, 2008;. Interestingly, we found that the GDNF heterozygote knockout (HET) mice consumed more alcohol than their WT littermates after a period of abstinence and exhibit increased CPP for alcohol (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009), suggesting an important role for the endogenous growth factor in the regulation of alcohol intake. To this end, we recently demonstrated that both the mRNA and protein levels of GDNF are increased in the VTA of rats after the first week of the 20% 2BC alcohol-drinking procedure (Ahmadiantehrani, Barak, & Ron, 2013).…”
Section: Protective Signaling Pathwaysmentioning
confidence: 87%
“…Blood samples were stored at −80°C, until BECs were determined using an NAD-ADH enzymatic assay (Carnicella et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor (GDNF) is a protein that is essential for the maintenance and survival of dopamine (DA) neurons (Boger et al, 2006) and can inhibit microglial activation (Rocha, Cristovão, Campos, Fonseca, & Baltazar, 2012). Additionally, preclinical evidence suggests that infusion of GDNF into the ventral tegmental area (VTA) blocks the acquisition and expression of alcohol-induced conditioned place preference (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Barak, Carnicella, Yowell, & Ron, 2011), rapidly reduces alcohol intake (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009, Carnicella, Amamoto, & Ron, 2009Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008), and blocks alcohol reinstatement following extinction (Carnicella et al, 2008). Furthermore, endogenous levels of GDNF have been found to negatively regulate the rewarding effect of alcohol after a period of abstinence (Carnicella, Ahmadiantehrani, et al, 2009;Carnicella, Amamoto, et al, 2009).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%
“…Additionally, preclinical evidence suggests that infusion of GDNF into the ventral tegmental area (VTA) blocks the acquisition and expression of alcohol-induced conditioned place preference (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Barak, Carnicella, Yowell, & Ron, 2011), rapidly reduces alcohol intake (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009, Carnicella, Amamoto, & Ron, 2009Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008), and blocks alcohol reinstatement following extinction (Carnicella et al, 2008). Furthermore, endogenous levels of GDNF have been found to negatively regulate the rewarding effect of alcohol after a period of abstinence (Carnicella, Ahmadiantehrani, et al, 2009;Carnicella, Amamoto, et al, 2009). In one human study, GDNF serum levels measured peripherally were found to be significantly reduced in alcohol-dependent patients versus healthy controls and to be negatively associated with measures of tolerance and withdrawal (Heberlein et al, 2010).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%